Pelaksanaan Standar Sistem Informasi Manajemen Sekolah Menengah Pertama se Kecamatan Padang Utara - Muhammad Arif Rahman; Anisah Anisah (Jurnal Bahana Manajemen Pendidikan, 2020)
The purpose of this research is to find information about the Implementation of Management Information System Standards for Middle School in North Padang District. This is a descriptive study. The population was 129 teachers or education personnel and the study sample was 68 teachers or education personnel taken by purpose random sampling. The instrument of this study was a questionnaire with a Likert scale model that had been tested for validity and reliability. The collected data is analyzed using the average formula (average). The results of this study indicate that the Implementation of Management Information System Standards for Middle Schools in Padang Utara District reaches quite good categories with an average score of 74.83%.